2022
DOI: 10.1038/s41419-022-04975-7
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analyses identify the anti-fibrotic role of lncRNA TP53TG1 in IPF

Abstract: Long non-coding RNA (lncRNA) was reported to be a critical regulator of cellular homeostasis, but poorly understood in idiopathic pulmonary fibrosis (IPF). Here, we systematically identified a crucial lncRNA, p53-induced long non-coding RNA TP53 target 1 (TP53TG1), which was the dysregulated hub gene in IPF regulatory network and one of the top degree genes and down-regulated in IPF-drived fibroblasts. Functional experiments revealed that overexpression of TP53TG1 attenuated the increased expression of fibrone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Former evidences reported that these p53 may promote fibrosis by inducing autophagy resistance in alveolar epithelial cells [ 34 , 35 ]. The involvement of p53 signaling pathway was previously reported in human lung samples of SSc-ILD and IPF, but not fHP and other CTD-ILDs [ 10 , 36 , 37 ], and its activation was proven to promote lung fibrosis resolution in aged mice [ 38 ], which is also reflected in our research. Consistently, our study indicated that p53 may contribute to progressive fibrosis in three ILDs and is a therapeutic target.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Former evidences reported that these p53 may promote fibrosis by inducing autophagy resistance in alveolar epithelial cells [ 34 , 35 ]. The involvement of p53 signaling pathway was previously reported in human lung samples of SSc-ILD and IPF, but not fHP and other CTD-ILDs [ 10 , 36 , 37 ], and its activation was proven to promote lung fibrosis resolution in aged mice [ 38 ], which is also reflected in our research. Consistently, our study indicated that p53 may contribute to progressive fibrosis in three ILDs and is a therapeutic target.…”
Section: Discussionsupporting
confidence: 83%
“…Former evidences reported that these p53 may promote fibrosis by inducing autophagy resistance in alveolar epithelial cells [34,35]. The involvement of p53 signaling pathway was previously reported in human lung samples of SSc-ILD and IPF, but not fHP and other CTD-ILDs [10,36,37],…”
Section: Evaluation Of Tissue-infiltrating Immune Cellsmentioning
confidence: 67%
“…TPRG1-AS1 was significantly enriched by MYH9 protein antibody compared with IgG-controls (Figure 3C and 3D), demonstrating a direct interaction between TPRG1-AS1 and MYH9 protein in HASMCs. In addition to TPRG1-AS1, 2 other lncRNAs MAFG-AS1 33 and TP53TG1 34 with high abundance in HASMCs (Figure S10A), previously reported to bind to MYH9 protein in other type cells, also interacted with MYH9 protein in HASMCs (Figure S10B). To further validate the interaction of TPRG1-AS1 with MYH9 protein in HASMCs, we performed chromatin isolation by RNA purification assay, an optimized method for the identification of lncRNA-bound proteins.…”
Section: Resultsmentioning
confidence: 70%
“…For the induction of a fibrotic cell model, we employed transforming growth factor beta (TGF-b) stimulation, a method well-established in the literature for simulating a fibrosis response in human fibroblasts (20,30). We used ACTA2 expression via qPCR as our primary readout, due its recognition in the literature as a critical marker of myofibroblasts and activated fibroblasts, key players in fibrotic disease progression across various organs, including the lungs (12)(13)(14)(15)(16)(17)(18)(19)(20). Optimal in vitro treatment doses were determined by conducting dose-response experiments and assessing cytotoxicity in our model system using the lactate dehydrogenate (LDH) release cytotoxicity assay (Figure S7).…”
Section: Reversal Of Fibrotic Gene Signature In Patient Pulmonary Fib...mentioning
confidence: 99%